Marine Actinomycetes-derived Natural Products - Yang, Chengfang; Qian, Rui; Xu, Yao; Yi, Junxi; Gu, Yiwen; Liu, Xiaoyu; Yu, Haobing; Jiao, Binghua; Lu, Xiaoling; Zhang, Wei (Current Topics in Medicinal Chemistry, 2019)
Actinomycetes is an abundant resource for discovering a large number of lead compounds, which play an important role in microbial drug discovery. Compared to terrestrial microorganisms, marine actinomycetes have unique metabolic pathways because of their special living environment, which has the potential to produce a variety of bioactive substances. In this paper, secondary metabolites isolated from marine actinomycetes are reviewed (2013-2018), most of which exhibited cytotoxic, antibacterial, and antiviral biological activities.
Keywords: Marine actinomycetes